Comparison of rat bone healing following intra-alveolar grafting with organic or inorganic bovine bone particles - Romeu Felipe Elias Calixto; Juliana Mazzonetto Teófilo; Luiz Guilherme Brentegani; Teresa Lamano (Universidade Estadual de Campinas, 2016)
Aim: This study compared, histometrically, the alveolar bone healing after grafting rats extraction socket with particles of organic or inorganic bovine bone. Method: The volume fraction of grafted materials and bone trabeculae was estimated in histologic images at the end of the 2nd and 9th weeks post-operatively by a differential point-counting method. Results: Particles of both materials were observed partially filling the cervical alveolar third and the volume fraction of inorganic graft was larger than that of organic graft 2 and 9 weeks following implantation. Although evoking neither a foreign-body reaction nor a persisting inflammatory response, both materials delayed bone healing. By the 2nd week, the delay was more pronounced in the animals grafted with inorganic than in those grafted with organic bone, but only in the animals whose inorganic graft occupied more than 50% of the cervical third. By the 9th week, despite the greater volume fraction of inorganic graft the percent of bone healing was similar to that observed in the animals grafted with organic bone. Conclusion: The degree of impairment of bone healing resulted from combination of factors such as type of material, its relative amount and the phase of the reparational process.